Pennisetum setaceum (Forssk.) Chiov. (Poaceae), nueva localidad para la flora ibérica. - Devesa, Juan Antonio; Arnelas, Itziar (Acta Botanica Malacitana, 2006)
Pennisetum setaceum (Forssk.) Chiov. (Poaceae), new locality for the Iberian Peninsula Palabras clave. Pennisetum, Poaceae, corología, Córdoba, Andalucía Occidental, Península Ibérica. Key words. Pennisetum, Poaceae, chorology, Cordoba, Western Andalusia, Iberian Peninsula.